Generation of the magnetic field in the compressible plasma streams - Kozlov, A.N. (Вопросы атомной науки и техники, 2008)
Results of the numerical simulations of the compressible plasma flows in the modified quasi-steady plasma accelerator with longitudinal magnetic field are presented. The investigations are carried out within the framework of the one-component two-dimensional MHD-model of the axial-symmetrical plasma flows taking into account of the finite conductivity of the medium. Features of the compressible streams at an outlet from accelerator are revealed in the presence of a longitudinal field and rotation of plasma. Generation of a magnetic field on a conic shock wave is observed. Представлено результати чисельного дослідження компресійних потоків плазми у модифікованому квазістаціонарному плазмовому прискорювачі з подовжнім магнітним полем. Дослідження проведено у рамках однорідинної двомірної МГД-моделі вісесиметричних течій плазми з урахуванням кінцевої провідності сердовища. Виявлено особливості компресіонних потоків на виході з прискорювача при наявності подовжнього поля й обертання плазми. Спостережується генерація магнітного поля на канонічній ударній хвилі Представлены результаты численного исследования компрессионных потоков плазмы в модифицированном квазистационарном плазменном ускорителе с продольным магнитным полем. Исследования проведены в рамках одножидкостной двумерной МГД-модели осесимметричных течений плазмы с учетом конечной проводимости среды. Выявлены особенности компрессионных потоков на выходе из ускорителя при наличии продольного поля и вращения плазмы. Наблюдается генерация магнитного поля на конической ударной волне.